Cell Cycle Regulatory Functions of the KSHV Oncoprotein LANA - Wei, Fang; Gan, Jin; Wang, Chong; Zhu, Caixia; Cai, Qiliang (Frontiers in Microbiology, 2016)
Manipulation of cell cycle is a commonly employed strategy of viruses for achieving a favorable cellular environment during infection. Kaposi’s sarcoma-associated herpesvirus (KSHV), the primary etiological agent of several human malignancies including Kaposi’s sarcoma (KS) and primary effusion lymphoma (PEL), encodes several oncoproteins that deregulate normal physiology of cell cycle machinery to persist with endothelial cells and B cells and subsequently establish a latent infection. During latency, only a small subset of viral proteins is expressed. LANA (Latency-associated nuclear antigen) is one of the latent antigens shown to be essential for transformation of endothelial cells in vitro. It has been well demonstrated that LANA is critical for the maintenance of latency, episome DNA replication, segregation and gene transcription. In this review, we summarize recent studies and address how LANA functions as an oncoprotein to steer host cell cycle-related events including proliferation and apoptosis by interacting with various cellular and viral factors, and highlight the potential therapeutic strategy of disrupting LANA-dependent signaling as targets in KSHV-associated cancers.